If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3ky + -12kz + 24kw = 0 Reorder the terms: 24kw + 3ky + -12kz = 0 Solving 24kw + 3ky + -12kz = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '3k'. 3k(8w + y + -4z) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'k' equal to zero and attempt to solve: Simplifying k = 0 Solving k = 0 Move all terms containing k to the left, all other terms to the right. Simplifying k = 0Subproblem 2
Set the factor '(8w + y + -4z)' equal to zero and attempt to solve: Simplifying 8w + y + -4z = 0 Solving 8w + y + -4z = 0 Move all terms containing k to the left, all other terms to the right. Add '-8w' to each side of the equation. 8w + y + -8w + -4z = 0 + -8w Reorder the terms: 8w + -8w + y + -4z = 0 + -8w Combine like terms: 8w + -8w = 0 0 + y + -4z = 0 + -8w y + -4z = 0 + -8w Remove the zero: y + -4z = -8w Add '-1y' to each side of the equation. y + -1y + -4z = -8w + -1y Combine like terms: y + -1y = 0 0 + -4z = -8w + -1y -4z = -8w + -1y Add '4z' to each side of the equation. -4z + 4z = -8w + -1y + 4z Combine like terms: -4z + 4z = 0 0 = -8w + -1y + 4z Simplifying 0 = -8w + -1y + 4z The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
k = {0}
| q(q+7)=0 | | 1-4p=-2(5p-1)+5 | | 2x+3y-2=5 | | -15=b-16 | | (2c-9)(c-1)=0 | | 31.25/25= | | 16x^2-36=-72 | | 2(x-7)+5=-9 | | 6s^4t^3-12s^3t^4=0 | | n(n-9)=0 | | 6x+7yx+9y=0 | | y^2+y-112=0 | | j(j-8)=0 | | 25/31.25= | | -9m=18 | | 4m(m-8)=0 | | 6=-4y+18 | | b^5+10b^4=0 | | 1/4x-2/5=5/6 | | (w-8)(3w+7)=0 | | 4-(2x+3)=5x-8 | | 1=v-8 | | -5-4r=-(1-2r) | | -9=2+p | | 8x-(5-x)+2(3x-4)=2 | | 3x^2=-18 | | 3r-4=5(r-1) | | 3k=45 | | 2(7/2)+y=11 | | 3(x-2)=-31+4x | | 8m+m-m-3m+2m=14 | | 3(2x+5)-5= |